PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ETNOSAINS TERINTEGRASI VIRTUAL SIMULATION DAN AUGMENTED REALITY (ETNOVAR) UNTUK MENINGKATKAN KETERAMPILAN 4C - Fahada, Qaddara; Anugrah, Muhammad; Ezha, Sephianti Dwika; Wiji, Wiji (UIN AR-RANIRY, 2026)
The 4C skills (Critical Thinking, Collaboration, Communication, Creativity) are essential for navigating Industrial Revolution 4.0 and digital transformation, distinguishing human intelligence from automation. The 4C skills can create a generation that is independent, innovative, and adaptive to rapid change. Despite their importance, development often remains suboptimal due to poorly facilitated learning. This study aims to enhance these skills by developing EtnoVAR, a virtual simulation integrated with Augmented Reality based on the ethnoscience of making peuyeum. Using the ADDIE (analysis, design, development, implementation, evaluate) method with 28 grade XI science students, the research involved rigorous expert validation and needs analysis. The feasibility test yielded a score of 95% (highly valid). Effectiveness testing via N-gain reached 0.92, indicating high effectiveness. Furthermore, questionnaires confirmed a substantial increase in students' 4C skills and high satisfaction levels. In conclusion, EtnoVAR is highly effective in improving 4C skills. Its strength lies in merging cutting-edge technology with local culture, transforming abstract concepts into an engaging, practical learning experience. This innovation ensures students remain independent, innovative, and adaptive to global challenges.